Camping Ground Potential To Improve Mangrove Beach Tourism Marketing - Lubis, Muhammad Rizki; Ramadhan, Ikhlas (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Mangrove Beach has many tourist attractions and is one of the choices for marine tourism. With various attractions offered, Mangrove Beach has a camping ground as one of the supporting accommodations for the attractions offered. The purpose of this study was to analyze the potential of the camping ground owned by Mangrove Beach to increase tourism marketing. This study is a descriptive study with a qualitative approach with Miles and Huberman data analysis techniques. Based on the results of the study, it was concluded that the potential for camping ground at Mangrove Beach, Serdang Bedagai Regency is the only beachside camping ground in Serdang Bedagai and its surroundings, has a very large area for setting up tents, there are sunset attractions, there are 2 homestay units as supporting accommodation, free camping ground fees if you bring personal equipment, has educational tours related to mangroves where this is one of the attractions for visitors, and there are fishermen who offer various catches that can be a choice of culinary visitors.